Catalytic Hydroalkylation of Allenes. Issue 49 (13th November 2017) - Lee, Mitchell; Nguyen, Mary; Brandt, Chance; Kaminsky, Werner; Lalic, Gojko
Abstract: We have developed a catalytic method for the hydroalkylation of allenes using alkyl triflates as electrophiles and silane as a hydride source. The reaction has an excellent substrate scope and is compatible with a wide range of functional groups, including esters, aryl halides, aryl boronic esters, sulfonamides, alkyl tosylates, and alkyl bromides. We found evidence for a reaction mechanism that involves unusual dinuclear copper ally complexes as catalytic intermediates. The unusual structure of these complexes provides a rationale for their unexpected reactivity. Abstract : A catalytic method was developed for the hydroalkylation of allenes using alkyl triflates as electrophiles and silane as a hydride source. The reaction has an excellent substrate scope and is compatible with a wide range of functional groups, including esters, aryl halides, aryl boronic esters, sulfonamides, alkyl tosylates, and alkyl bromides. The reaction mechanism appears to involve unusual dinuclear copper ally complexes as catalytic intermediates.